Pluralist Internationalism in our Time - Chung, Ryoa (Les ateliers de l'éthique / The Ethics Forum, 2013)
In his 2012 book On Global Justice, Mathias Risse makes an invaluable contribution to the literature on theories of global justice. In this paper, I offer a critique of the fourth and final part of the book, entitled “Global Justice and Institutions,” which deals with the standing of the state within the pluralist internationalism defended by the author. My focus here is on the justification of the state system and the discussion on utopian ideals. I agree with Risse that the state remains the inescapable political structure that any serious theory of global justice must internalize within its conceptual framework. However, I differ from Risse’s approach in that I place greater emphasis on the historical contingency of the state system, including how prescriptions of global justice reflect historical contingencies stemming from globalization. From this point of view, pluralist internationalism should then be understood as a conceptual paradigm that mirrors its own historical contingency as embedded in our current world order. This recognition of the historical contingency of the state system serves two important purposes. One, it is a bulwark against any tendency to discredit too quickly the philosophical and practical relevance of ideal theory. Two, it buttresses the stance that we might still have the moral duty to pursue the goal of global justice beyond pluralist internationalism.